2023
DOI: 10.3390/ijms24032795
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Interleukin-1 Family in Complications of Prematurity

Abstract: Preterm birth is a major contributor to neonatal morbidity and mortality. Complications of prematurity such as bronchopulmonary dysplasia (BPD, affecting the lung), pulmonary hypertension associated with BPD (BPD-PH, heart), white matter injury (WMI, brain), retinopathy of prematurity (ROP, eyes), necrotizing enterocolitis (NEC, gut) and sepsis are among the major causes of long-term morbidity in infants born prematurely. Though the origins are multifactorial, inflammation and in particular the imbalance of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 277 publications
0
8
0
Order By: Relevance
“…The precursor of IL‐38 requires N‐terminal cleavage, which can bind to receptors and recruit downstream factors, thereby exerting biological activities. Inflammatory response plays an important role in human physiological and pathological processes, and the cytokine IL‐38 has been identified to have a protective role in diseases 8–10 . Therefore, this review searched public databases for relevant publications of IL‐38, aiming to summarize the role and mechanism of IL‐38 in various system diseases and to discuss the future directions of prevention and treatment.…”
Section: Overview Of Interleukin‐38 (Il‐38)mentioning
confidence: 99%
“…The precursor of IL‐38 requires N‐terminal cleavage, which can bind to receptors and recruit downstream factors, thereby exerting biological activities. Inflammatory response plays an important role in human physiological and pathological processes, and the cytokine IL‐38 has been identified to have a protective role in diseases 8–10 . Therefore, this review searched public databases for relevant publications of IL‐38, aiming to summarize the role and mechanism of IL‐38 in various system diseases and to discuss the future directions of prevention and treatment.…”
Section: Overview Of Interleukin‐38 (Il‐38)mentioning
confidence: 99%
“…On the one hand, it is directly involved in lung in ammation and immune response, resulting in lung injury. On the other hand, positive feedback acts on immune cells, resulting in in ammatory cascade reaction and aggravating lung injury [27,28]. IL6T is the receptor of cytokines IL-6 and IL-27.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that TSG-6 was negatively correlated with gestational week of delivery, and IL1B and IL6R were negatively correlated with neonatal weight. It has been shown that inflammation, and in particular an imbalance of pro- and anti-inflammatory mediators, is recognized as a key factor in the pathophysiology underlying preterm birth as well as neonatal disease [ 45 ].…”
Section: Discussionmentioning
confidence: 99%